1994
DOI: 10.2307/3869974
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium meliloti Lipooligosaccharide Nodulation Factors: Different Structural Requirements for Bacterial Entry into Target Root Hair Cells and Induction of Plant Symbiotic Developmental Responses

Abstract: Rhizobium meliloti produces lipochitooligosaccharide nodulation NodRm factors that are required for nodulation of legume hosts. NodRm factors are O-acetylated and N-acylated by specific C16-unsaturated fatty acids. nodL mutants produce non-O-acetylated factors, and nodFE mutants produce factors with modified acyl substituents. Both mutants exhibited a significantly reduced capacity to elicit infection thread (IT) formation in alfalfa. However, once initiated, ITs developed and allowed the formation of nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
173
1
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(186 citation statements)
references
References 0 publications
9
173
1
3
Order By: Relevance
“…Aberrant, abortive infection threads are formed when Nod factor is supplied in a structurally incomplete form, or if Nod factor perception is disrupted 18,19,42 . An S. meliloti nodF nodL double mutant that produces Nod factor that lacks the acetyl substituent and has an altered acyl chain cannot effectively invade plant cells, and induces approximately 20% of colonized root hairs to form infection threads 19,42 . Those infection threads that are formed are aberrant and 'sac-like', and abort before reaching the base of the root hair cell 19 (FIG.…”
Section: Sinorhizobium Meliloti Succinoglycan Biosynthesismentioning
confidence: 99%
“…Aberrant, abortive infection threads are formed when Nod factor is supplied in a structurally incomplete form, or if Nod factor perception is disrupted 18,19,42 . An S. meliloti nodF nodL double mutant that produces Nod factor that lacks the acetyl substituent and has an altered acyl chain cannot effectively invade plant cells, and induces approximately 20% of colonized root hairs to form infection threads 19,42 . Those infection threads that are formed are aberrant and 'sac-like', and abort before reaching the base of the root hair cell 19 (FIG.…”
Section: Sinorhizobium Meliloti Succinoglycan Biosynthesismentioning
confidence: 99%
“…Interestingly,, in the interaction with the noc/Fi? mutuant it was shown that, once the infection thread has passed the epidermis of the alfalfa root, infection proceeds normally (Ardourel et al, 1994). This indicates that in alfalfa also the control receptor is only active in the epidermis.…”
Section: Sym2mentioning
confidence: 95%
“…The activity in depolarization of NodRm-IV(C18: 1,8), carrying a saturated acyl chain, was severely reduced compared with that of NodRm-IV (C16:2,S), carrying the unsaturated acyl group specific for R. meliloti (Felle et aL, 1995), Although 0-acetylation of the nonreducing end sugar had no effect on the maximum of depolarization, the response to the O-acetylated factor was initially faster. Furthermore, markedly fewer infection threads were initiated by R. meliloti mutated in nodE or nodL which produces Nod factors that do not contain the appropriate unsaturated fatty acid or the O-acetyl group, respectively (Ardourel et aL, 1994), A strain mutated both in nodE and nodL, secreting Nod factors lacking the O-acetyl group and containing an inappropriate fatty acid had completely lost the abilitj' to induce infection threads (Adourel et aL, 1994), Substitutions at the reducing end of the Nod factors can have a dramatic effect on the activity to induce the epidermal responses. For example, desulphation of the NodRm factors reduces at least 1000-fold their activity to induce root hair deformation, ENOD12 expression and membrane potential depolarization on alfalfa (Journet et aL, 1994;Felle et aL, 1995), In addition, R. meliloti strains mutated in nodH, producing only non-sulphated NodRm factors, are unable to induce infection thread formation in alfalfa .…”
Section: Nod Factor Perception In the Epidermismentioning
confidence: 99%
See 2 more Smart Citations